2016
DOI: 10.1167/iovs.16-20191
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Structural Changes in Myopic Choroidal Neovascularization After Treatment With Antivascular Endothelial Growth Factor Over 1 Year

Abstract: Thinning of subfoveal choroid without alteration in CVI was observed in eyes with mCNV treated with anti-VEGF therapy over 12 months. This finding may be explained by mechanical stretching in response to globe expansion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…4 Recently, CVI was introduced to enable the measurement of the choroidal vasculature outside bPPA by means of image binarization of SD-OCT B-scans. 9,[11][12][13][14][15] Similarly, recent studies have calculated choroidal vascularity by using SD-OCT images to assess diurnal variation and IOP-related change. 10,17 The present study showed reduced choroidal vasculature outside the bPPA, which corresponded to MvD_P in glaucomatous eyes based on image binarization of SD-OCT. Also, these findings suggest that CVI measurement can serve as a potential noninvasive tool for the quantification of choroidal vasculature in glaucoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Recently, CVI was introduced to enable the measurement of the choroidal vasculature outside bPPA by means of image binarization of SD-OCT B-scans. 9,[11][12][13][14][15] Similarly, recent studies have calculated choroidal vascularity by using SD-OCT images to assess diurnal variation and IOP-related change. 10,17 The present study showed reduced choroidal vasculature outside the bPPA, which corresponded to MvD_P in glaucomatous eyes based on image binarization of SD-OCT. Also, these findings suggest that CVI measurement can serve as a potential noninvasive tool for the quantification of choroidal vasculature in glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in vivo quantification of the choroidal vasculature outside the bPPA based on the reflectivity of the choroidal structure as imaged by spectral-domain OCT (SD-OCT) was newly introduced. [9][10][11][12][13][14][15][16][17] Specifically, there are a number of reports regarding the clinical relevance of the choroidal vascularity index (CVI) for various retinal diseases. 9,[11][12][13][14][15][16] The purpose of the present study was to determine the total choroidal area (TCA) and CVI by means of image binarization of SD-OCT images and to compare them between glaucomatous eyes with and without OCT-A-determined MvD_P.…”
mentioning
confidence: 99%
“…20 In eyes from diabetic patients and eyes with exudative AMD, there were decreased CVI with no significant change in CT. 26,28,29 CVI was also shown to provide additional information to CT in terms of longitudinal choroidal structural changes in diseases such as panuveitis 20 ; Vogt-Koyanagi-Harada (VKH) disease 25 ; central serous chorioretinopathy (CSCR) 24 ; and myopic choroidal neovascularization. 27 Changes in L/C ratio or a similar index called L/S ratio (ratio of choroidal luminal area to stromal area) were investigated and found to yield valuable information in normal physiologic conditions including diurnal variation 22 and dynamic exercise 23 as well as in a number of ocular diseases including exudative AMD 21 ; polypoidal choroidal vasculopathy (PCV) 34 ; CSCR 32,33 ; VKH disease 30,31 ; and retinitis pigmentosa. 36 In this study, we compared the agreement between markers of choroidal vascularity (CVI and L/C ratio) measured by twoimage binarization techniques and significant differences were found between the two measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it may not truly reflect the functional aspect of choroidal blood flow. Novel imaging techniques such as OCT angiography and other biomarkers of choroidal vascularity, such as the choroidal vascularity index (CVI), 31,32 may further clarify the role of choroidal blood flow in MMD pathogenesis. Lastly, due to the cross-sectional design, causality cannot be inferred.…”
Section: Discussionmentioning
confidence: 99%